The Proses pembuatan filter pada mesin pp sadiment cartridge - Muhamad Busrol Karim, Busrol (Universitas Majalengka, 2021)
Abstract Water is a very important need for all living things in general for drinking water, water is processed through processing or without treatment that meets health requirements and can be directly consumed by humans, from the national socio-economic survey data (Susenas) in the last 12 years, there has been an increase. drastic water users, so it needs to be underlined that water treatment must be in accordance with the SOP so as not to endanger health. In order to ensure that the water is protected from even the smallest dirt, a filter cartridge is made, by undergoing several stages of production where the main ingredient uses polypropylene. The initial stage where the material liquefaction process uses a barrel exstruder at a predetermined room temperature, then the nozzle is sprayed on the rolling filter machine to make the filter shape which then goes to the filter cutting machine to be cut according to the desired filter specification length, in the process of making this filter cartridge we know some variables that we can analyze including how much time it takes to increase the temperature of the extruder barrel (465 seconds), flow rate (0.183 m/s & 0.39 m/s), flow nozzle (0.527 m3/s), how many heat released (69,750,000 Joules), the effect of rpm on the rolling machine, and how long it takes at the start of cutting the filter product (1.12 minutes) Keywords: water filter, filter cartridge, filter machine.